Drawing in times of pandemic: A dialogue in two voices accompanied by Jean-Luc Nancy - López Fdz. Cao, Marián (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2021)
The text explores a reflection on the act of drawing in relation to the creative process that occurred during the confinement derived from COVID19, between April and June 2020. Elements such as attention, gaze, care, holding, attachment and pleasure emerge in the creative act, especially when vulnerability and unpredictability arise all around. Based on theoretical references such as Jean-Luc Nancy, a consideration of the creative potential in times of uncertainty is addressed
Keywords: Creative process; Pandemic; Drawing; Gaze; Attachment